The Rubber Hand Illusion in a Patient with Hand Disownership. (September 2013) - van Stralen, Haike E; van Zandvoort, Martine J E; Kappelle, L Jaap; Dijkerman, H Chris
A 78-year-old patient with a right hemispheric sensorimotor ischemic stroke suffered from problems in ownership of her left arm (somatoparaphrenia). After recovering from motor weakness, however, body ownership problems remained present. To assess whether disturbed feelings of ownership coincided with an enhanced or diminished susceptibility for gaining ownership over a foreign hand, we applied the 'Rubber Hand Illusion' (RHI) to the ipsi- and contralesional hand. The RHI was significantly stronger for the contralesional left arm than for the right arm. In addition, solely visual exposure to the left rubber hand was sufficient to elicit strong feelings of ownership over the rubber hand. These findings suggest that disturbances in the feeling of body ownership allow a foreign hand to be incorporated more easily.